Inhibition of Giardia intestinalis by extracellular factors from Lactobacilli: an in vitro study - Pérez, Pablo Fernando (2001)
The aim of the present work was to evaluate the effect of spent culture supernatants of different strains of lactobacilli on giardia trophozoites. The growth of Giardia intestinalis strain WB, as well as the attachment to the human intestinal epithelial cell line Caco-2, was evaluated by using proliferation and adhesion assays with radiolabeled parasites. In addition, scanning electron microscopy and flow cytometric analysis were performed. The effect of spent culture supernatants from lactobacilli was strain dependent. Lactobacillus johnsonii La1 significantly inhibited the proliferation of G. intestinalis trophozoites. Although the effect was strongly pH dependent, it was not simply due to lactic acid. According to flow cytometric analysis, trophozoites were arrested in G1 phase but neither significant necrosis nor apoptosis could be detected. Bacterial cells or their spent culture supernatants were unable to modify trophozoite attachment to Caco-2 cells. However, trophozoites treated with spent culture supernatants had little, if any, proliferative capacity. These results suggest that La1 produces some substance(s) able to inhibit proliferation of Giardia trophozoites. Partial characterization of the factors involved in the antigiardiasic action showed that they have a low molecular mass and are inactivated by heating. On this basis, it seems worthwhile to explore how colonization of the proximal small bowel with these lactic acid bacteria could interfere with giardiasis in vivo.